Penggunaan Negative Pressure Wound Therapy (NPWT) terhadap Diabetic Foot Ulcer - Rinda Apriani; Debie Dahlia; Dikha Ayu Kurnia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to conduct a literature review related to research results that discusses the effectiveness of NPWT on diabetic foot ulcers (DFU). The method used is a systematic review method from online databases such as Scopus, ClinicalKey, ClinicalKey Nursing, EBSCOhost, Proquest, ScienceDirect, Springer Link, Pubmed, and SAGE Journals using the keywords diabetes mellitus, negative pressure wound therapy, NPWT, and diabetic foot ulcer. The search uses the boolean logic